Effects of artificial inoculation on trait correlations with resistance to Fusarium ear rot and fumonisin contamination in maize. Issue 4 (18th June 2021) - Butoto, Eric N.; Marino, Thiago P.; Holland, James B.
Abstract: Breeding for resistance to Fusarium ear rot (FER; Fusarium verticillioides Nirenberg) and fumonisin (FUM) contamination in maize ( Zea mays L.) is labor intensive, time consuming, and expensive. The objective of this study is to explore three possible shortcuts to improve the efficiency of breeding for resistance to FER and FUM: relying on natural instead of artificial inoculation of Fusarium verticillioides, selecting inbred lines per se instead of topcross hybrids, and using grain test weight (TW) as an indirect selection criterion. We selected the 27 most resistant and 26 most susceptible S0:1 lines from the third cycle of a broad‐based recurrent selection population and topcrossed them to a common inbred line. The resulting topcross hybrids were evaluated in three North Carolina environments under artificial and natural inoculation of F. verticillioides . The entry‐mean heritabilities for FER and FUM are considerably reduced under natural conditions compared to artificial inoculation; therefore, artificial inoculation should be practiced for efficient selection for resistance. We found a high correlation between FER and FUM content of S0:1 lines per se and their topcross hybrids, suggesting that selection among early generation inbred lines per se is an efficient method to improve resistance in their topcross hybrids. The TW of inoculated S0:1 lines per se was strongly and negatively correlated with FER and FUM of their topcross hybrids, suggesting that TW can be utilized as an indirect selection criterion to improve resistance to FER and FUM contamination. Core Ideas: Can we make breeding for resistance to Fusarium ear rot more efficient? Artificial inoculation is necessary for accurate breeding selections. We can select for resistance in inbred lines to improve hybrids. We can select for higher test weight in inbred lines to improve hybrid resistance.